2001
DOI: 10.1542/peds.108.6.e112
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Vaccinations, Vaccination Timing, and Risk of Type 1 Diabetes Mellitus

Abstract: ABSTRACT. Objectives. To evaluate suggested associations between childhood vaccinations, particularly against hepatitis B and Haemophilus influenzae type b, and risk of developing type 1 diabetes; and to determine whether timing of vaccination influences risk.Methods. We conducted a case-control study within 4 health maintenance organizations (HMOs) that participate in the Vaccine Safety Datalink project of the Centers for Disease Control and Prevention. Study eligibility was restricted to children who met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 16 publications
4
42
1
4
Order By: Relevance
“…The preliminary data found an odds ratio of 1.9 when the hepatitis B vaccine was given starting after two months, the average follow up was 22 months. A later analysis claims that immunization starting after 8 weeks of life was not associated with an increased risk of IDDM [32]. Approximately 75% of cases and controls were less than 6 years of age indicated that there should have been at least 3 or more years of follow up after immunization to detect the cases of vaccine induced IDDM.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary data found an odds ratio of 1.9 when the hepatitis B vaccine was given starting after two months, the average follow up was 22 months. A later analysis claims that immunization starting after 8 weeks of life was not associated with an increased risk of IDDM [32]. Approximately 75% of cases and controls were less than 6 years of age indicated that there should have been at least 3 or more years of follow up after immunization to detect the cases of vaccine induced IDDM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no support was found for the hypothesis that early BCG vaccination was protective [47,48]. A recent American case-control study confirmed this observation for the so called "traditional" vaccinations and provided data on newer vaccines including hepatitis B, acellular pertussis and varicella vaccines [49]. The balance between Th 1 and Th 2 lymphocytes and cytokines seems to be of importance in the expression of autoimmune diseases including Type 1 diabetes [50].…”
Section: Descriptive Epidemiology Of Type 1 Diabetes In Europementioning
confidence: 99%
“…This nationwide cohort, together to the prospective and independent ascertainment of vaccination history and the time of T1DM diagnosis overcame the risk of selection bias and recall bias [151]. De Stefano et al, in a case-control study, didn't support an association between any of the recommended childhood vaccines and increased risk of T1DM [152]. Similar results have been reported in a retrospective cohort study in active components of US Military between 2002-2008 [153].…”
Section: Vaccines and Risk Of T1dmmentioning
confidence: 53%